Adsorptive desulfurization of model fuel by S, N-codoped porous carbons based on polybenzoxazine. (15th April 2018) - Zhao, Rijie; Jin, Zuer; Wang, Jianlong; Zhang, Guoli; Zhang, Dongdong; Sun, Yahui; Guan, Taotao; Zhao, Jianghong; Li, Kaixi
Graphical abstract: Highlights: The S, N co-doped porous carbons were prepared based on polybenzoxazine. The porous carbons showed high capacity for adsorptive desulfurization of fuel oil. The porous carbons showed good selectivity in the adsorptive process for aromatic-containing model fuel. Abstract: S, N-codoped porous carbons (NSPCs) were synthesized from 4-cyanophenol, thiourea and formaldehyde based on benzoxazine chemistry with KOH chemical activation at different temperatures. The textural and chemical properties of NSPCs were characterized in detail by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), N2 adsorption-desorption isotherm, X-ray photoelectron spectroscopy (XPS) and elemental analysis. The resulting porous carbons possess high volume of pores smaller than 1.5 nm, which exhibit good adsorptive desulfurization performance with high maximum adsorptive capacity of dibenzothiophene (DBT) from 69.81 to 83.34 mg S/g. Furthermore, NSPC-2 shows good selectivity in adsorptive process for aromatic-containing model fuel, due to its abundant surface functionalities. More than 77% adsorption capacity of NSPC-2 can still be recovered after 5 times adsorptive experiments.